Legal System for Electoral Campaigns : A Comparative Study - Al Shawi, Sura (Journal of Legal Sciences, 2023)
Electoral campaigns are one of the stages of the electoral process, and it means the sum of the activities and activities carried out by the candidate or the political party within a period of time, usually one day or more before the polling date, according to the legislation. To vote for this candidate or party, and this process affects the results of the elections, whether parliamentary or presidential, because it targets the votes that lead the candidate or political party to a boost to the presidency of the state or the legislative authority, so that this right is not abused in promoting political ideas and visions, considering This is one of the branches of freedom of opinion and expression that is guaranteed by most constitutions. To ensure the freedom, integrity and fairness of elections, we find that the Iraqi law, as well as comparative laws, directly subject this process to some restrictions and limitations. This study focuses the light on the electoral campaign, its nature, foundations, objectives, and legal restrictions that apply within its limits, whether they are temporal. Or, spatial, financial and other regulatory restrictions in order to identify the shortcomings in some legislation and propose solutions to address them.